Pengaruh Audit Internal Dan Pengendalian Internal Terhadap Kinerja PT Sumber Graha Sejahtera Way Kanan Lampung - Yolanda, Jenny; Zanaria, Yulita; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to determine the influence of internal audit and internal control on the performance of PT Sumber Graha Sejahtera Way Kanan Lampung. The type of research used is quantitative research. The instrument used in this research is a questionnaire. Data analysis was carried out using multiple linear regression analysis. The research results show that Internal Audit has a positive and significant effect on the performance of PT SGS Way Kanan Lampung employees. Internal Control has a positive and significant effect on the performance of PT SGS Way Kanan Lampung employees. Internal Audit and Internal Control simultaneously have a significant effect on the performance of PT SGS Way Kanan Lampung employees